1991
DOI: 10.1001/archderm.1991.04510010118015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Regression in Merkel Cell (Neuroendocrine) Carcinoma of the Skin

Abstract: In two Japanese women, 68 and 88 years old, Merkel cell (neuroendocrine) carcinoma of the face developed. Their tumors regressed after biopsy was performed, a rare occurrence. Histological and electron microscopic examination showed apoptosis, cellular necrosis, and an infiltration composed mainly of lymphocytes in the tumors. These changes may have been related to the mechanism of regression. It is interesting that our two patients were women, as was another patient described with Merkel cell carcinoma regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Studies of primary and metastatic MCC that were observed to regress have demonstrated infiltration by immune cells, including CD4 + , CD8 + , and CD3 + T cells and macrophages [47,48,49]. An examination of tumors that subsequently partially or completely regressed after biopsy found a significant increase in T cells compared to tumors that did not regress [50].…”
Section: Clinical Coursementioning
confidence: 99%
“…Studies of primary and metastatic MCC that were observed to regress have demonstrated infiltration by immune cells, including CD4 + , CD8 + , and CD3 + T cells and macrophages [47,48,49]. An examination of tumors that subsequently partially or completely regressed after biopsy found a significant increase in T cells compared to tumors that did not regress [50].…”
Section: Clinical Coursementioning
confidence: 99%
“…Merkel cell carcinoma (MCC) is a rare malignant highly aggressive tumour arising from neuroendocrine cells 1 . Despite the aggressive course of MCC, 11 previous cases of regression in MCC have been reported in the English literature and four additional cases are only available in Japanese 2–9 …”
Section: To the Editormentioning
confidence: 99%
“…The estimated prevalence of spontaneous regression when considering all neoplastic disease has been reported as less than one case of regression in 60 000–100 000 neoplasms 10 . In a review of the English literature we have found 11 previously reported cases of partial/complete regression of MCC, three of them with nodal metastasis that also regressed 2–9 . In most cases regression of the primary tumour was preceded by a biopsy of the lesion; a procedure that may stimulate the immune system against neoplastic disease.…”
Section: To the Editormentioning
confidence: 99%
“…Over recent years, eight patients (five women and three men) with spontaneously regressing NCS have been reported; 3–9 in six of these, regression was related to cell‐mediated immunity, due to an abundant population of cytotoxic T lymphocytes (CD3+ , CD8+), and in four cases it was associated with a more favourable clinical course 4–7 . However, the patient reported by Rosso et al 1 .…”
mentioning
confidence: 98%